Find the value of the sum of the trigonometric functions $ \cot x+\cot \left( {{60}^{o}}+x \right)+\cot \left( {{120}^{o}}+x \right) $ ?
(a) $ \cot 3x $
(b) $ \tan 3x $
(c) $ 3\tan 3x $
(d) $ \dfrac{3-9{{\tan }^{2}}x}{3\tan x-{{\tan }^{3}}x} $
Answer
Verified
483k+ views
Hint: We start solving problem by using the result \[\cot \left( A+B \right)=\dfrac{\cot \left( A \right).\cot \left( B \right)-1}{\cot \left( A \right)+\cot \left( B \right)}\] for the terms given in $ \cot x+\cot \left( {{60}^{o}}+x \right)+\cot \left( {{120}^{o}}+x \right) $ . We substitute the values required in the equations obtained and we get the answer in cotangent functions. Since the given options are present in tangent functions, we use the fact that the tangent function is inverse of the cotangent function to get the final answer.
Complete step-by-step answer:
Given that we need to find the value of $ \cot x+\cot \left( {{60}^{o}}+x \right)+\cot \left( {{120}^{o}}+x \right) $ . Let us assume the value is ‘y’.
We have got $ y=\cot x+\cot \left( {{60}^{o}}+x \right)+\cot \left( {{120}^{o}}+x \right) $ ---(1).
We know that \[\cot \left( A+B \right)=\dfrac{\cot \left( A \right).\cot \left( B \right)-1}{\cot \left( A \right)+\cot \left( B \right)}\]. Let us substitute this in equation (1).
So, we have got $ y=\cot x+\dfrac{\cot \left( {{60}^{o}} \right).\cot x-1}{\cot \left( {{60}^{o}} \right)+\cot x}+\dfrac{\cot \left( {{120}^{o}} \right).\cot x-1}{\cot \left( {{120}^{o}} \right)+\cot x} $ ---(2).
We know that the values of $ \cot \left( {{60}^{o}} \right) $ and $ \cot \left( {{120}^{o}} \right) $ are $ \dfrac{1}{\sqrt{3}} $ and $ \dfrac{-1}{\sqrt{3}} $ . Let us substitute these in equation (2).
$\Rightarrow$ $ y=\cot x+\dfrac{\dfrac{1}{\sqrt{3}}.\cot x-1}{\dfrac{1}{\sqrt{3}}+\cot x}+\dfrac{\dfrac{-1}{\sqrt{3}}.\cot x-1}{\dfrac{-1}{\sqrt{3}}+\cot x} $ .
$\Rightarrow$ $ y=\cot x+\dfrac{\dfrac{\cot x-\sqrt{3}}{\sqrt{3}}}{\dfrac{1+\sqrt{3}\cot x}{\sqrt{3}}}+\dfrac{\dfrac{-\cot x-\sqrt{3}}{\sqrt{3}}}{\dfrac{-1+\sqrt{3}\cot x}{\sqrt{3}}} $ .
$\Rightarrow$ $ y=\cot x+\dfrac{\cot x-\sqrt{3}}{1+\sqrt{3}\cot x}+\dfrac{-\cot x-\sqrt{3}}{-1+\sqrt{3}\cot x} $ .
$\Rightarrow$ \[y=\cot x+\dfrac{\left( \left( \cot x-\sqrt{3} \right)\times \left( -1+\sqrt{3}\cot x \right) \right)+\left( \left( -\cot x-\sqrt{3} \right)\times \left( 1+\sqrt{3}\cot x \right) \right)}{\left( 1+\sqrt{3}\cot x \right)\times \left( -1+\sqrt{3}\cot x \right)}\].
$\Rightarrow$ \[y=\cot x+\dfrac{\left( -\cot x+\sqrt{3}{{\cot }^{2}}x+\sqrt{3}-3\cot x \right)+\left( -\cot x-\sqrt{3}-\sqrt{3}{{\cot }^{2}}x-3\cot x \right)}{-1+\sqrt{3}\cot x-\sqrt{3}\cot x+3{{\cot }^{2}}x}\].
$\Rightarrow$ \[y=\cot x+\dfrac{-8\cot x}{-1+3{{\cot }^{2}}x}\].
$\Rightarrow$ \[y=\dfrac{\left( \cot x\times \left( -1+3{{\cot }^{2}}x \right) \right)+\left( -8\cot x \right)}{-1+3{{\cot }^{2}}x}\].
$\Rightarrow$ \[y=\dfrac{-\cot x+3{{\cot }^{3}}x-8\cot x}{-1+3{{\cot }^{2}}x}\].
$\Rightarrow$ \[y=\dfrac{3{{\cot }^{3}}x-9\cot x}{-1+3{{\cot }^{2}}x}\].
$\Rightarrow$ \[y=\dfrac{3{{\cot }^{3}}x-9\cot x}{3{{\cot }^{2}}x-1}\]---(3).
We know that $ \cot x=\dfrac{1}{\tan x} $ . Let us substitute this in equation (3).
$\Rightarrow$ \[y=\dfrac{\left( \dfrac{3}{{{\tan }^{3}}x} \right)-\left( \dfrac{9}{\tan x} \right)}{-1+\left( \dfrac{3}{{{\tan }^{2}}x} \right)}\].
$\Rightarrow$ \[y=\dfrac{\left( \dfrac{3-9{{\tan }^{2}}x}{{{\tan }^{3}}x} \right)}{\left( \dfrac{-{{\tan }^{2}}x+3}{{{\tan }^{2}}x} \right)}\].
$\Rightarrow$ \[y=\dfrac{\left( \dfrac{3-9{{\tan }^{2}}x}{\tan x} \right)}{-{{\tan }^{2}}x+3}\].
$\Rightarrow$ \[y=\dfrac{3-9{{\tan }^{2}}x}{\left( \tan x \right)\times \left( -{{\tan }^{2}}x+3 \right)}\].
$\Rightarrow$ \[y=\dfrac{3-9{{\tan }^{2}}x}{3\tan x-{{\tan }^{3}}x}\].
∴ The value of $ \cot x+\cot \left( {{60}^{o}}+x \right)+\cot \left( {{120}^{o}}+x \right) $ is \[\dfrac{3-9{{\tan }^{2}}x}{3\tan x-{{\tan }^{3}}x}\].
So, the correct answer is “Option D”.
Note: Alternatively, we can check the options by assigning a value for ‘x’ which is between $ {{0}^{o}} $ and $ {{90}^{o}} $. Similarly, we can expect tangent, cosine and sine functions instead of given cotangent functions. Whatever the trigonometric function provided in the problem, we start and solve the problem by using the same procedure.
Complete step-by-step answer:
Given that we need to find the value of $ \cot x+\cot \left( {{60}^{o}}+x \right)+\cot \left( {{120}^{o}}+x \right) $ . Let us assume the value is ‘y’.
We have got $ y=\cot x+\cot \left( {{60}^{o}}+x \right)+\cot \left( {{120}^{o}}+x \right) $ ---(1).
We know that \[\cot \left( A+B \right)=\dfrac{\cot \left( A \right).\cot \left( B \right)-1}{\cot \left( A \right)+\cot \left( B \right)}\]. Let us substitute this in equation (1).
So, we have got $ y=\cot x+\dfrac{\cot \left( {{60}^{o}} \right).\cot x-1}{\cot \left( {{60}^{o}} \right)+\cot x}+\dfrac{\cot \left( {{120}^{o}} \right).\cot x-1}{\cot \left( {{120}^{o}} \right)+\cot x} $ ---(2).
We know that the values of $ \cot \left( {{60}^{o}} \right) $ and $ \cot \left( {{120}^{o}} \right) $ are $ \dfrac{1}{\sqrt{3}} $ and $ \dfrac{-1}{\sqrt{3}} $ . Let us substitute these in equation (2).
$\Rightarrow$ $ y=\cot x+\dfrac{\dfrac{1}{\sqrt{3}}.\cot x-1}{\dfrac{1}{\sqrt{3}}+\cot x}+\dfrac{\dfrac{-1}{\sqrt{3}}.\cot x-1}{\dfrac{-1}{\sqrt{3}}+\cot x} $ .
$\Rightarrow$ $ y=\cot x+\dfrac{\dfrac{\cot x-\sqrt{3}}{\sqrt{3}}}{\dfrac{1+\sqrt{3}\cot x}{\sqrt{3}}}+\dfrac{\dfrac{-\cot x-\sqrt{3}}{\sqrt{3}}}{\dfrac{-1+\sqrt{3}\cot x}{\sqrt{3}}} $ .
$\Rightarrow$ $ y=\cot x+\dfrac{\cot x-\sqrt{3}}{1+\sqrt{3}\cot x}+\dfrac{-\cot x-\sqrt{3}}{-1+\sqrt{3}\cot x} $ .
$\Rightarrow$ \[y=\cot x+\dfrac{\left( \left( \cot x-\sqrt{3} \right)\times \left( -1+\sqrt{3}\cot x \right) \right)+\left( \left( -\cot x-\sqrt{3} \right)\times \left( 1+\sqrt{3}\cot x \right) \right)}{\left( 1+\sqrt{3}\cot x \right)\times \left( -1+\sqrt{3}\cot x \right)}\].
$\Rightarrow$ \[y=\cot x+\dfrac{\left( -\cot x+\sqrt{3}{{\cot }^{2}}x+\sqrt{3}-3\cot x \right)+\left( -\cot x-\sqrt{3}-\sqrt{3}{{\cot }^{2}}x-3\cot x \right)}{-1+\sqrt{3}\cot x-\sqrt{3}\cot x+3{{\cot }^{2}}x}\].
$\Rightarrow$ \[y=\cot x+\dfrac{-8\cot x}{-1+3{{\cot }^{2}}x}\].
$\Rightarrow$ \[y=\dfrac{\left( \cot x\times \left( -1+3{{\cot }^{2}}x \right) \right)+\left( -8\cot x \right)}{-1+3{{\cot }^{2}}x}\].
$\Rightarrow$ \[y=\dfrac{-\cot x+3{{\cot }^{3}}x-8\cot x}{-1+3{{\cot }^{2}}x}\].
$\Rightarrow$ \[y=\dfrac{3{{\cot }^{3}}x-9\cot x}{-1+3{{\cot }^{2}}x}\].
$\Rightarrow$ \[y=\dfrac{3{{\cot }^{3}}x-9\cot x}{3{{\cot }^{2}}x-1}\]---(3).
We know that $ \cot x=\dfrac{1}{\tan x} $ . Let us substitute this in equation (3).
$\Rightarrow$ \[y=\dfrac{\left( \dfrac{3}{{{\tan }^{3}}x} \right)-\left( \dfrac{9}{\tan x} \right)}{-1+\left( \dfrac{3}{{{\tan }^{2}}x} \right)}\].
$\Rightarrow$ \[y=\dfrac{\left( \dfrac{3-9{{\tan }^{2}}x}{{{\tan }^{3}}x} \right)}{\left( \dfrac{-{{\tan }^{2}}x+3}{{{\tan }^{2}}x} \right)}\].
$\Rightarrow$ \[y=\dfrac{\left( \dfrac{3-9{{\tan }^{2}}x}{\tan x} \right)}{-{{\tan }^{2}}x+3}\].
$\Rightarrow$ \[y=\dfrac{3-9{{\tan }^{2}}x}{\left( \tan x \right)\times \left( -{{\tan }^{2}}x+3 \right)}\].
$\Rightarrow$ \[y=\dfrac{3-9{{\tan }^{2}}x}{3\tan x-{{\tan }^{3}}x}\].
∴ The value of $ \cot x+\cot \left( {{60}^{o}}+x \right)+\cot \left( {{120}^{o}}+x \right) $ is \[\dfrac{3-9{{\tan }^{2}}x}{3\tan x-{{\tan }^{3}}x}\].
So, the correct answer is “Option D”.
Note: Alternatively, we can check the options by assigning a value for ‘x’ which is between $ {{0}^{o}} $ and $ {{90}^{o}} $. Similarly, we can expect tangent, cosine and sine functions instead of given cotangent functions. Whatever the trigonometric function provided in the problem, we start and solve the problem by using the same procedure.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE